CMOS analog filter design using the Proportional Source Transconductances Integrator. (May 2018) - Silva, Rodrigo Barros da; D'Eça, Lucas Costa; Carvalho, Matheus Neves; Santana, Edson Pinto; Cunha, Ana Isabela Araújo
Abstract: This work assesses the applicability of a compact CMOS current-mode companding integrator in the design of analog continuous-time filters with high linearity. The companding integrator is based on the proportionality between the source transconductances of the input and output MOS transistors and is independent of the inversion level of the devices. The circuit has been designed in CMOS 130 nm technology with approximately 90 μm 2 total active area including biasing elements. According to simulation results the integrator performs a useful frequency bandwidth of up to 4 MHz and a third order intermodulation distortion smaller than −47 dB for input amplitudes ranging from 100 nA to 1 μA. The small and large signal responses and the third order intermodulation, among other features, have also been analyzed through simulation for a fourth order low-pass filter and a sixth order bandpass filter. Performance is compared with a CMOS log-domain integrator and filter.